Extraction of Collagen from Chicken Feet with Various Acidic Solutions and Soaking Time - Prayitno, Prayitno (ANIMAL PRODUCTION, 2007)
The objective of this research was to know the ability of various acidic solutions on dissolving collagen  chicken feet, with different soaked time.  Each acid 5 percent (v/v), collagen extraction was done by washing chicken feet and then cutted into small pieces and finally grinded.  Every 100 gram treatment was soaked in acetic acid (a1), citric acid (a2), lactic acid (a3) and hydrochloric acid (a4), for 12, 24 and 36 hours.  Precipitated collagen in the filtrate was 5 percent NaOH to reach the neutral pH (pH 7).  Collagen precipitate was separated by filtration usingfilter paper and then  rendement was calculated, HPLC was used to determin amino acid composition, and SDS-PAGE was use determin the type of collagen.  This experiment use factorial completely randomized design (CRD) 4 x 3 and three time replication.   Result showed that lactic acid has highest capability to dissolve collagen, while citric acid the lowest.  Combination of acid solution and soaking time had significant (P<0.01) effect on dissolving collagen of chicken feet.  Extracted collagen in all acid solution, hassame amino acid, composition but different in percentage of amino acid molecules.  Collagen type in treatment combination was the same, but for soaking time of 36 hours revealed some peptide band.  Lactic acid had highest capability of collagen extraction in chicken feet than citric acid, acetic acid and hydrochloric acid with soaking time of 12, 24 and 36 hours.  It was estimated that extracted collagen can be grouped to type I consisted of two chain of a1. (Animal Production 9(2): 99-104 (2007)  Key Words : Chicken feet, acids, soaking time, collagen